Cost Burden of Cardiovascular Hospitalization and Mortality in ATHENA‐Like Patients With Atrial Fibrillation/Atrial Flutter in the United States - Naccarelli, Gerald V. (Clin Cardiol, 2010)
BACKGROUND: The ATHENA trial (A placebo‐controlled, double‐blind, parallel arm Trial to assess the efficacy of dronedarone 400 mg bid for the prevention of cardiovascular Hospitalization or death from any cause in patiENts with Atrial fibrillation/atrial flutter) demonstrated that dronedarone reduced the risk of cardiovascular (CV) hospitalization/death by 24% (P < 0.001) in patients with atrial fibrillation (AF) and atrial flutter (AFL). HYPOTHESIS: In order to estimate the cost savings associated with dronedarone use, we estimated the costs associated with CV hospitalizations and inpatient mortality in a large cohort of ATHENA‐like patients. METHODS: In this retrospective analysis, we evaluated the cost of CV hospitalization/mortality in real‐world ATHENA‐like patients without heart failure and with employer‐sponsored Medicare supplemental insurance in the United States. Patients similar to those in ATHENA (age ≥ 70 years with AF/AFL and ≥ 1 stroke risk factor, without heart failure) who were hospitalized between January 2, 2005, and January 1, 2007, were identified from the MarketScan databases from Thomson Reuters. Health care costs were evaluated during the 12 months following the index hospitalization. RESULTS: The analysis included 10 200 ATHENA‐like patients. Hospitalization for CV causes occurred in 53.9% of patients, with a total of 6700 CV hospitalizations for fatal/nonfatal causes. The most common nonfatal causes of CV hospitalizations were AF/other supraventricular rhythm disorders (20.2% of all CV hospitalizations), congestive heart failure (CHF; 14.3%), and transient ischemic attack (TIA)/stroke (10.7%). Mean costs per CV hospitalization for nonfatal causes were $10908. Inpatient deaths from CV causes occurred in 264 (2.6%) patients; the most common causes of CV inpatient death were intracranial/gastrointestinal hemorrhage (24.2% of CV deaths), TIA/stroke (17.0%), and CHF (15.9%). Mean hospitalization costs per CV inpatient death were $18 565. CONCLUSIONS: Health care costs associated with CV hospitalizations and inpatient deaths among ATHENA‐like patients in the US are high. Novel antiarrhythmic therapies such as dronedarone, with the potential to reduce CV hospitalizations/mortality in similar patients, could decrease health care costs if adopted in clinical practice. Copyright © 2010 Wiley Periodicals, Inc.